Forests, Tribals and the Voice of Dissent: The Story of a Social Actor - Namami Sharma (Space and Culture, India, 2013)
This is a biography of an activist who has been working in the interiors of Madhya Pradesh with the indigenous people. He has been living amongst the tribal communities and has contributed significantly in the people’s struggle for resource rights. He is one of the very few activists who has been quoted by different writers but is not written about. This article, thus, makes a humble endeavour to trace his life and his commitment towards the cause of tribal rights.